An Analytical Study of Masters Dissertations on the Balme Library, University of Ghana, Legon - Fosu, V.K.; Alemna, A.A. (African Journal of Library, Archives & Information Science, 2006)
This paper analyses masters dissertations written on the Balme Library, University of Ghana by students of the Department of Information Studies, University of Ghana fram 1998-2005, with a view to ascertaining how the management of Balme Library has implemented the recommendations from the dissertations. The analysis takes the form of the type and year of dissertation, subject of dissertation, and whether written by Balme Library staff or not. The findings indicate that most of the recommendations in the dissertations have not been implemented by the library. One of the reasons for this is that the Balme Library did not even know of the findings and recommendations. Some suggestions have been made to overcome this problem, including the need for staff of the Balme Library to supervise some of such dissertations or, failing this, and/or the need for the management of the library to, at least, be made aware of studies and recommendations relating to the Balme Library.
Keywords: Masters Dissertations; Balme Library; University of Ghana